2012
DOI: 10.1105/tpc.112.104125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PAN2 by Quantitative Proteomics as a Leucine-Rich Repeat–Receptor-Like Kinase Acting Upstream of PAN1 to Polarize Cell Division in Maize

Abstract: Mechanisms governing the polarization of plant cell division are poorly understood. Previously, we identified pangloss1 (PAN1) as a leucine-rich repeat-receptor-like kinase (LRR-RLK) that promotes the polarization of subsidiary mother cell (SMC) divisions toward the adjacent guard mother cell (GMC) during stomatal development in maize (Zea mays). Here, we identify pangloss2 (PAN2) as a second LRR-RLK promoting SMC polarization. Quantitative proteomic analysis identified a PAN2 candidate by its depletion from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 44 publications
4
131
0
Order By: Relevance
“…Formation of a GMC (produced by an unknown mechanism) causes the flanking cells, called subsidiary mother cells (SMCs), to position their nuclei and divide toward the GMC, resulting in one SC adjacent to each GC. Two LRR receptor-like kinases, PANGLOSS1 (PAN1) and PAN2, are strong polarity markers that play an important role in orientating the asymmetric division of SMCs (Cartwright et al, 2009;Zhang et al, 2012).…”
Section: Extrinsic Cue-mediated Protein Pan1mentioning
confidence: 99%
“…Formation of a GMC (produced by an unknown mechanism) causes the flanking cells, called subsidiary mother cells (SMCs), to position their nuclei and divide toward the GMC, resulting in one SC adjacent to each GC. Two LRR receptor-like kinases, PANGLOSS1 (PAN1) and PAN2, are strong polarity markers that play an important role in orientating the asymmetric division of SMCs (Cartwright et al, 2009;Zhang et al, 2012).…”
Section: Extrinsic Cue-mediated Protein Pan1mentioning
confidence: 99%
“…Phenotypically similar, but unlinked, pan2 mutants (Zhang et al 2012) were also assessed to test the hypothesis that the pan genes influence the disease response through their known effect on stomatal morphology or related pathways. We tested pan1 and pan2 mutants for NLB and Stewart's wilt in replicated, multiyear trials and found a significant genotype effect (P-value ,0.0001) for both diseases.…”
Section: Association Mappingmentioning
confidence: 99%
“…This result indicates that unlike some developmental transcription factors, the TSH1 protein probably does not traffic from cell to cell (Whipple et al, 2010). In other examples, stably transformed maize lines expressing FP fusion proteins have also been used to study biosynthetic proteins (Christensen et al, 2013, Falcone Ferreyra et al, 2012 and proteins that regulate asymmetric cell divisions during leaf development (Humphries et al, 2011, Zhang et al, 2012. Transcriptional fusions have also been used to make hormone responsive reporters (Lee et al, 2009).…”
Section: Application Of Fluorescent Protein Marker Lines In Protein Lmentioning
confidence: 99%